MENAKAR â€œKADAR POLITISâ€ AISYIYAH - Dzuhayatin, Siti Ruhaini (Yinyang: Jurnal Studi Islam Gender dan Anak, 2009)
after the fall out of New Order and entering reformation era, women’s conventional organization face a reality of contestationgender construct from all side, include NGO and other groups like Islam conservative group that want total separation of women and mendomain. State cant become ‘patron’ to justify an idealized gender constructs. In this context, Aisyiyah have to option: first, still as organizationthat based on purely practical issues with the consequence labeled as ‘status quo’ and conservative organization. Second, Aisyiyah have toopen itself to reality of social injustice than conserve ‘idealization of serene family’. Third, Aisyiyah have thrown away administrative routinethat depleted much energy. Fourth, Aisyiyah have to respond to women strategic issues, nationally or internationally